The Learning Motivation and Physical Fitness of University Students During the Implementation of the New Normal Covid-19 Pandemic - Eko Bagus Fahrizqi; Rachmi Marssheilla Agus; Rizki Yuliandra; Aditya Gumantan (STKIP Muhammadiyah Kuningan, 2021)
Sports are related to health and achievement, which cannot be separated from several factors, including motivation to learn and physical fitness. This research was conducted to determine the level of learning motivation and students’ physical fitness during the Covid-19 pandemic. The method used in this research is descriptive quantitative method by using survey methods. The subjects of this research were students of Sports Education Study Program at Universitas Teknokrat Indonesia from batch 2017 until 2019. The instruments used were a questionnaire and a measurement test. The results of the study showed that the level of students’ learning motivation of batch 2017 was 74.23%, which was lower than Sports Students of batch 2018, 85.68% and batch 2019, 84.87% respectively. Meanwhile, the level of students’ physical fitness from all three batches were categorized into the moderate classification. The conclusion of the study showed that the level of learning motivation of Sports Education students was still in a high category and there was no significant difference in terms of physical fitness levels between students during the Covid-19 pandemic.